WORK PRODUCTIVITY ENHANCEMENT IN HOME INDUSTRY PIA CAKE ”XYZ” - Lala Intan Gemala Sari; Meizul Zuki; Yusril Dany (Jurnal Agroindustri, 2013)
The research objective is to obtain the new method with highest productivity; determine the normal and basis hour in order to get the best working hour with highest productivity; and to determine number of worker need in each section based on its workload to get the balance in production line. Time measurement was done using a technique based on stopwatch and workload measurement analysis method. The balancing of production line was done by trial and error method. Initial conditions in production line indicate an imbalance with 2312,18 seconds idle time, 51,60% efficiency of production line and 48,39% balance delay. The balancing of production line resulted 1585,77 seconds of idle time, 45% efficiency of production line and 55% balance delay. There are eight permanent workers in this home industry with labor productivity at station I is 6,42% units / man-hour before repairs and 8,57% units / man-hour after repairs, resulted the increase in productivity by 33,48%. Labor productivity at station II, III and IV before repairs is 87,5% and after repairs is 116,62% resulted the increase in labor productivity by 33,28%.